PENGUKURAN KUALITAS WEBSITE BADAN KEPEGAWAIAN NEGARA KANTOR REGIONAL II DENGAN MENGGUNAKAN METODE WEBQUAL 4.0 - harianja, filemon edwin; Sudarmaningtyas, Pantjawati; Mujayana, Marya (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Civil Service Agency (BKN) Regional Office II is an organizational unit of government. To support the implementation of the basic tasks BKN Kanreg II uses a system of information in the form of websites. But the interest of website visitors BKN Kanreg II considerably less than they had hoped, can be seen until 11 February 2016, with an average of 150 visits per week. This is far from the expected parties BKN Kanreg II which has a target of 350 visits per week. BKN party Kanreg II had never done an evaluation of the website owned in terms of quality.In the evaluation process, the measurement of the quality of the website BKN Kanreg II using WebQual 4.0. Variables used in this study include Usability Quality, Information Quality, Interaction Quality and Quality Website variables. The population used is the BKN employees Kanreg II and Disnaker with a sample that used as many as 161 respondents.Results from the study showed that variables Usability Quality has a greater influence than the variable Information Quality and Quality Interaction variables with the t value of 3.241. Recommendations generated in this study is the BKN Kanreg II further improve the website in terms of usability, in order to get a better quality website.Keywords: WebQual 4.0, Quality, Usability Quality, Information Quality, Interaction Quality, Website Quality.